2019
DOI: 10.1152/ajpgi.00395.2018
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular release of ATP promotes systemic inflammation during acute pancreatitis

Abstract: In the current study, we explored the role of extracellular ATP (eATP) in promoting systemic inflammation during development of acute pancreatitis (AP). Release of extracellular (e)ATP was evaluated in plasma and bronchoalveolar lavage fluid (BALF) of mice with experimental acute pancreatitis (AP). Prophylactic intervention using apyrase or suramin was used to understand the role and contribution of eATP in pancreatitis-associated systemic injury. AP of varying severity was induced in C57BL/6 mice using 1-day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…P2X 4 receptor has failed to demonstrate a significant contribution to the final outcome in a mouse model of traumatic lung injury [ 210 ]. Dixit et al reported recently that the non-specific P2-antagonist suramin alleviated systemic and lung inflammation as well as lung injury in mouse models of acute pancreatitis [ 211 ]. Further, they observed increased plasma levels of ATP, suggesting that ATP was involved in remote activation of the pulmonary immune system, and indeed i.v.…”
Section: The Role Of P2 Receptors In Lung Diseasementioning
confidence: 99%
“…P2X 4 receptor has failed to demonstrate a significant contribution to the final outcome in a mouse model of traumatic lung injury [ 210 ]. Dixit et al reported recently that the non-specific P2-antagonist suramin alleviated systemic and lung inflammation as well as lung injury in mouse models of acute pancreatitis [ 211 ]. Further, they observed increased plasma levels of ATP, suggesting that ATP was involved in remote activation of the pulmonary immune system, and indeed i.v.…”
Section: The Role Of P2 Receptors In Lung Diseasementioning
confidence: 99%
“…Macrophages need two distinct stimuli to activate caspase-1, leading to release of active IL-1b. One stimulus (Toll-like receptor [TLR] ligands) induces transcription, and a second stimulus (ATP) induces IL-1b secretion (Dixit et al, 2019;Ferrari et al, 1997b;Netea et al, 2009;Riteau et al, 2012). During the inflammation-activation phase, stressed and activated cells can release ATP and acute cell injury or death will cause massive ATP release into the extracellular milieu.…”
Section: Discussionmentioning
confidence: 99%
“…In AP, the initial inflammatory process leads to migration of monocytes and neutrophils into the pancreas ( Dixit et al, 2019 ). Neutrophils have been proposed to play crucial roles in the early phase of disease development, contributing to activation of trypsinogen and progression to severe AP ( Habtezion, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Acute pancreatitis (AP) is initiated with inappropriate activation of pancreatic enzymes and subsequent local and systemic inflammatory responses ( Kang et al, 2014 ; Dixit et al, 2019 ). Inflammatory mediators released from injured acinar cells and immune cells mediate pancreatic injury and exacerbation of AP ( Pandol et al, 2007 ; Zhang et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%